Mengenal Iman dan Takwa Melalui Dakwah Bil Hikmah Anak dalam Al-Quran di Sekolah - Rosmidar Rosmidar; Robiatul Adawiyah; Yunita Sari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Faith and piety education from an early age is the main foundation in forming a child's personality that is noble and spiritually strong. Schools as formal educational institutions have an important role in introducing these values through the da'wah bil hikmah approach. This study aims to examine how the da'wah bil hikmah method in the Qur'an can be implemented in the school environment to instill the values of faith and piety in children. With a da'wah approach that is gentle, wise, and in accordance with the child's psychological development, the process of introducing Islamic values becomes more touching and meaningful. The results of the study showed that da'wah bil hikmah applied through Qur'anic stories, teacher role models, and the habit of worship can shape the character of children who are religious, empathetic, and responsible. These findings strengthen that schools are a strategic medium in the process of internalizing the values of faith and piety through an approach full of wisdom.